Versatile chimeric antigen receptor platform for controllable and combinatorial T cell therapy. (1st January 2020) - Feldmann, Anja; Hoffmann, Anja; Bergmann, Ralf; Koristka, Stefanie; Berndt, Nicole; Arndt, Claudia; Rodrigues Loureiro, Liliana; Kittel-Boselli, Enrico; Mitwasi, Nicola; Kegler, Alexandra; Lamprecht, Chris; González Soto, Karla Elizabeth; et al.
ABSTRACT: Chimeric antigen receptor (CAR) T cells show remarkable therapeutic effects in some hematological malignancies. However, CAR T cells can also cause life-threatening side effects. In order to minimize off-target and on-target/off-tumor reactions, improve safety, enable controllability, provide high flexibility, and increase tumor specificity, we established a novel humanized artificial receptor platform termed RevCARs. RevCAR genes encode for small surface receptors lacking any antigen-binding moiety. Steering of RevCAR T cells occurs via bispecific targeting molecules (TMs). The small size of RevCAR-encoding genes allows the construction of polycistronic vectors. Here, we demonstrate that RevCAR T cells efficiently kill tumor cells, can be steered by TMs, flexibly redirected against multiple targets, and used for combinatorial targeting following the "OR" and "AND" gate logic.